Aesthetic rehabilitation on fractured and altered passive eruption anterior teeth: A case report - Rahadyan SJ. Pramudita; Yulita Kristanti; Margareta Rinastiti; Hendargo Pribadi (Journal of Dentomaxillofacial Science, 2021)
Objective: This case report aims to present the management of crown fractures with pulpal exposure caused by traumatic injury and a condition called gummy smile or altered passive eruption (APE), through a multidisciplinary approach. Case Report: A 24-year-old male patient came to the Dental Conservation Clinic RSGM Prof Soedomo FKG UGM, complained of broken teeth and pain in the upper front tooth due to an accident. #12 and #21 experienced horizontal discontinuity to the dentine surface and some lines on the labial surface and #11 underwent a fracture with exposure of the pulpal tissue. The patient wants to take care of broken teeth and improve his smiles. Results: A treatment plan was formulated, which consisted of a stepwise treatment including endodontic treatment, crown lengthening, prefabricated glass-fiber post followed by a core build-up, and finally, direct composite to achieve patient satisfaction. Conclusion: The careful planning of a multidisciplinary approach such as endodontics, periodontics, and direct restorations can treat patients with complex aesthetic complaints relating to problems with the tooth and its soft tissues, and immediate restoration for providing a fast, predictable, economical, yet satisfactory result to improves patient self-confidence.